Theosophy and the Study of Religion - Stang, Charles M., (Aries Book Series ;, 2024)
Since its emergence in the nineteenth century, the Theosophical Society has wielded enormous influence across diverse fields, none more so than the study of religion. This volume explores this legacy in North America, Europe, and India, demonstrating its impact on the conceptualization of "religion" and its influence on methods of comparison. Unveiling overlooked entanglements, the volume challenges standard narratives in the history of religious studies and interrogates the deliberate neglect of theosophy's influence in the "secular" academy. In doing so, the work confronts lingering ghosts, urging a reappraisal that enriches the study of religion and offers prescriptions for its future.